The Role of Calcination Temperature Variation in The Sol–Gel Synthesis of Hydroxyapatite - Siswanto; Hikmawati, Dyah; Falentina, Winda Dwi (Indonesian Applied Physics Letters, 2025)
This study aims to synthesize hydroxyapatite using the sol–gel method with variations in calcination temperature. The hydroxyapatite precursor was derived from eggshell. The egg shell powder was milled using High Energy Milling (HEM) for 20 hours, producing particles measuring 54.84 nm based on Particle Size Analyzer (PSA) results. A 1.67 M calcium dioxide solution obtained from the coral powder was reacted with a 1 M phosphoric acid solution through the sol–gel process. The resulting gel was dehydrated at 110 °C and then calcined at temperatures ranging from 450 to 900 °C for 5 hours. The synthesized products were characterized using X-ray Diffraction (XRD). The results indicated that calcination at 550 °C for 5 hours produced the most stable hydroxyapatite phase, with a volume fraction of 90.8%, a crystallinity degree of 39.8%, and a crystal size of 32.09 nm.